PENGARUH LOCUS OF CONTROL, FINANCIAL LITERACY, DAN INCOME TERHADAP KEPUTUSAN INVESTASI EMAS (STUDI EMPIRIS PADA NASABAH PRODUK MULIA DI PT. PEGADAIAN (PERSERO) CABANG AMBON) - Mualim, Al’Fisra Salvia; Basuki, Ferry Hendro; Latuamury, Jabida (Jurnal Akuntansi, 2023)
The purpose of this study is to find out whether there is an influence of locus of control, financial literacy, and income on the gold investment decisions. This type of research uses quantitative methods with a sample of 50 respondents. Sources of data obtained in this study from distributing questionnaires. While the data analysis technique used in this study uses multiple linear regression analysis. The results of this study indicate that locus of control has a positive and significant effect on gold investment decisions. Financial literacy has a positive and significant effect on gold investment decisions. Income has a positive and significant effect on gold investment decisions